The p38β Mitogen-activated Protein Kinase Possesses an Intrinsic Autophosphorylation Activity, Generated by a Short Region Composed of the α-G Helix and MAPK Insert - Beenstock, Jonah (American Society for Biochemistry and Molecular Biology, 2014)
Protein kinases are regulated by a large number of mechanisms that vary from one kinase to another. However, a fundamental activation mechanism shared by all protein kinases is phosphorylation of a conserved activation loop threonine residue. This is achieved in many cases via autophosphorylation. The mechanism and structural basis for autophosphorylation are not clear and are in fact enigmatic because this phosphorylation occurs when the kinase is in its inactive conformation. Unlike most protein kinases, MAP kinases are not commonly activated by autophosphorylation but rather by MEK-dependent phosphorylation. Here we show that p38β, a p38 isoform that is almost identical to p38α, is exceptional and spontaneously autoactivates by autophosphorylation. We identified a 13-residue-long region composed of part of the αG-helix and the MAPK insert that triggers the intrinsic autophosphorylation activity of p38β. When inserted into p38α, this fragment renders it spontaneously active in vitro and in mammalian cells. We further found that an interaction between the N terminus and a particular region of the C-terminal extension suppresses the intrinsic autophosphorylation of p38β in mammalian cells. Thus, this study identified the structural motif responsible for the unique autophosphorylation capability of p38β and the motif inhibiting this activity in living cells. It shows that the MAPK insert and C-terminal extension, structural motifs that are unique to MAPKs, play a critical role in controlling autophosphorylation.